Towards Energy Security and Sustainability in Indonesia: Exploring The Waqf-Based Potential - Lisa Listiana; Lu’liyatul Mutmainah (Global Review of Islamic Economics and Business, 2022)
It is ironic to note that Indonesia remains a net importer of energy, which has been one of the basic needs of the Indonesians. As the efforts to decrease the energy import and  to secure energy supply, including through Renewable Energy (RE) development which has already started, the gap between the target and the actual is observable and acknowledged in existing studies or official reports by the authorities. Alignment between Islamic Finance (IF) and Renewable Energy can be observed, as both ideally have a preference for the earth and environment-friendly program. They align with several Sustainable Development Goals (SDGs), including SDG 7 on affordable and clean energy, SDG 10 on reduced inequality, SDG 13 on climate action, and SDG 17 on partnership on the goals. That is why this study aims to explore the opportunities and challenges of waqf-based renewable energy in Indonesia. To this end, a Focus Group Discussion (FGD) with 15 key informants from 12 different institutions was conducted by Waqf Center for Indonesian Development and Studies (WaCIDS). Notable views from relevant stakeholders, the representatives of both waqf and the RE sector, are complemented by an open-ended questionnaire, which was circulated during the session. Data is analyzed using thematic analysis with the assistance of Atlas.ti software. As a pioneer study that relates waqf and renewable energy in Indonesia, this study provides an avenue for further research and implementation. This study is expected to offer theoretical and practical references on waqf and RE discourse. As the waqf-related stakeholders may gain insight into entering the RE projects, the RE practitioners may also acknowledge the potential of waqf as part of financing alternatives. Hopefully, this study can benefit the policymakers and the pivotal stakeholders in seeking a solution to secure and sustain energy in Indonesia.